2021
DOI: 10.3390/su13105452
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in the Field of Education: State of the Art

Abstract: COVID-19 has produced a transformation in society that has, in turn, influenced the field of education. The purpose of this study was to analyze the influence of COVID-19 on education using the Web of Science database. A methodology based on bibliometrics was used. Specifically, a scientific mapping of the literature was carried out, as well as a co-word analysis on the state of the question. The analysis included 940 publications. The results show that the institution with the highest volume of production in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 39 publications
1
28
0
4
Order By: Relevance
“…Moreover, this study adds value to the current line of research on the effects of cooperative learning in times of COVID-19 [40]. First, the study contributes to the higher education literature in general, since it examines the effect of the COVID-19 pandemic on good teaching, satisfaction, and student performance in relation to two different learning paths.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, this study adds value to the current line of research on the effects of cooperative learning in times of COVID-19 [40]. First, the study contributes to the higher education literature in general, since it examines the effect of the COVID-19 pandemic on good teaching, satisfaction, and student performance in relation to two different learning paths.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, SciMAT (University of Granada, Granada, Spain) is a tool used to analyse scientific maps in a longitudinal framework that allows measuring the centrality and density of each research topic using strategic diagrams [71]. Different authors have already used this tool in areas such as tourism [72,73], sustainability [74,75], business [76], and education [77,78], among others, with the intention of finding associations and new research trends.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, researchers may have preferred English for their work to have a widespread impact. From another perspective, it can be regarded as a natural consequence of WOS's focus on the Anglo-Saxon field (Corell-Almuzara et al, 2021).…”
Section: Distribution Of Articles By Publication Languagementioning
confidence: 99%
“…The researcher found out that the countries' contribution in Europe and America to the literature was high. Corell-Almuzara et al (2021) analyzed the impact of COVID-19 on education and analyzed 940 publications in the WOS directory. The results of the research indicated that the publications were predominantly in English and US-based.…”
Section: Introductionmentioning
confidence: 99%